Population-based study of influenza and invasive meningococcal disease among Greek children during the COVID-19 pandemic - Theoklis Zaoutis; Vassiliki Papaevangelou; Danai Ktena; Eleni Kourkouni; Flora Kontopidou; Kassiani Gkolfinopoulou; Kalliopi Papadima; Theano Georgakopoulou; Ioanna Magaziotou; Anastasia Andreopoulou; Georgina Tzanakaki (BMJ Publishing Group, 2022)
Background Aiming to the containment of the coronavirus disease 2019 (COVID-19) pandemic, governments worldwide have implemented a series of non-pharmaceutical interventions. Many of them and especially school closures have impacted the circulation of multiple airborne pathogens among children and adolescents. This study investigates the incidence of influenza and invasive meningococcal disease among children aged 0-14 years in Greece during the COVID-19 pandemic.Methods Data regarding the number of influenza-like illness cases, influenza-related paediatric intensive care unit (PICU) admissions and invasive meningococcal disease cases among children 0-14 years old were obtained from the National Public Health Organization. The incidence of the two diseases during the COVID-19 pandemic period (2020/2021) was compared with that of the six preceding seasons (2014-2019).Results A notable decrease was observed in both influenza and invasive meningococcal disease cases during the period 2020/2021 compared with the years 2014-2019. The mean annual rate of influenza-like illness cases and influenza-related PICU admissions in children 0-14 years old has reduced by 66.9% and 100%, respectively, while the mean annual invasive meningococcal disease rate has declined by 70%. Both weekly influenza-like illness and monthly invasive meningococcal disease rates were significantly decreased.Conclusions The activity of influenza and invasive meningococcal disease in the children and adolescents of Greece has decreased during the COVID-19 pandemic period. Reduced transmission is likely related to the public health measures that were implemented to control the pandemic. The value of these measures may have relevance to the future management of influenza or invasive meningococcal disease epidemics.